The Impact of International Human Rights Law on National Judicial Systems : A Comparative Analysis (International Forum of Researchers and Lecturers, 2025)
This study examines the impact of international human rights law on national judicial systems through a comparative analysis. The research aims to explore how international human rights norms influence domestic court decisions and the extent to which national judicial systems incorporate these norms into their legal frameworks. Using a qualitative comparative approach, this study analyzes judicial decisions from multiple countries with varying legal traditions. The findings reveal significant differences in the reception and application of international human rights law, influenced by historical, cultural, and political contexts. The study concludes that while some judicial systems demonstrate a strong commitment to integrating international human rights norms, others show resistance due to sovereignty concerns or differing legal philosophies. These findings highlight the complex relationship between international human rights law and national judicial practices, offering insights for policymakers, legal practitioners, and human rights advocates to enhance the effectiveness of human rights protections globally.